2020
DOI: 10.3390/antiox9121195
|View full text |Cite
|
Sign up to set email alerts
|

Revalorization of Broccoli By-Products for Cosmetic Uses Using Supercritical Fluid Extraction

Abstract: The agri-food industry is currently one of the main engines of economic development worldwide. The region of Murcia is a reference area in Europe for the cultivation of fruits and vegetables and produces the bulk of Spanish exports of broccoli (Brassica oleracea var. italica). The processing of fresh produce generates a huge number of by-products that represent an important economic and environmental problem when discarded. In this work, an advanced extraction technique using environmentally friendly solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The large amounts of broccoli waste have a negative effect on the agricultural environment and food security. Some studies have revealed that significant amounts of bioactive compounds and essential nutrients are present in the broccoli byproducts, such as phenolic compounds, glucosinolates, flavonoids, carotenoids, and sterols [5][6][7][8]. The bioactive compounds are extra-nutritional components with the capacity of modulating metabolic processes, and some of them hold antioxidant, anti-microbial, or anti-inflammatory properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The large amounts of broccoli waste have a negative effect on the agricultural environment and food security. Some studies have revealed that significant amounts of bioactive compounds and essential nutrients are present in the broccoli byproducts, such as phenolic compounds, glucosinolates, flavonoids, carotenoids, and sterols [5][6][7][8]. The bioactive compounds are extra-nutritional components with the capacity of modulating metabolic processes, and some of them hold antioxidant, anti-microbial, or anti-inflammatory properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While we were interested in broccoli by-products—in particular, leaves—that are seldom utilised for food. Broccoli leaves, similar to florets, are characterised by a high content of nutrients (proteins, vitamin C, minerals, and trace elements) and bioactive compounds (glucosinolates, phenolic acids, and flavonoids) [ 19 , 20 ]. Although perceived as a waste product, they might be consumed as a valuable fresh product or as sources of phytonutrients, allowing to obtain added-value baked products [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The non-thermal technologies found were: solid-state fermentation, supercritical fluid extraction, ultrasounds, high pressure, hydrostatic pressure, electro-technologies, enzyme-assisted extraction, and light stress. Most of the investigations found (70%) were on fruit by-products or the wine and distillate industry, with only two studies related to vegetables (onion and broccoli) [ 79 , 80 , 81 ].…”
Section: Effect Of Non-thermal Technologies On Fruit and Vegetable By-products Polyphenolsmentioning
confidence: 99%
“…The market for natural cosmetics is growing due to the importance of sustainable development and protecting the environment. Manufacturers present an interest in recovering bioactive compounds from F&V by-products for reducing the environmental impact of waste and for converting them into particularly valuable sources of extracts for cosmetic usage [ 79 , 155 ]. In addition, the potential of food and agricultural residues (rich sources of different classes of compounds with valuable active principles) for the preparation of pharmaceutical and bioactive compounds is gaining importance, taking the environmental impact of the overall production process into account [ 19 , 156 ].…”
Section: Trends and Challenges For Fruit And Vegetable By-products Application In Food Systemsmentioning
confidence: 99%
See 1 more Smart Citation